Designing spirits: Transitioning from attachments that kill to attachments that save. Issue 1 (2nd January 2017) - Garzon, Juan Carlos
Abstarct: This article seeks to explore a speculative design practice that emerges from a modern understanding of animism. Design as it is taught in most universities around the world, perpetuates an Eurocentric view of the world and promotes unsustainability. Faced with the massive changes to earthly habitation brought upon by the Anthropocene, design must be transformed into a practice based on care. The Western construction of the concept of nature that was imposed over others via colonialism can be revised. Other understandings of nature offer interesting possibilities for human habitation and can open a pathway to reframe what it means to be human. Animism is thus presented as a way of thinking from the borderlands and a platform from where design can be transformed.